Enhancing Homogeneity and Particle Size Reduction in Coffee–Creamer Mixtures Using Fluidized Bed Mixer - Nanang Ruhyat; Erna Multahada; Alfa Firdaus Sirait (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2025)
This study investigates the application of a fluidized bed mixer to improve the homogeneity, particle size distribution, and moisture reduction of coffee and creamer powder mixtures. The research focuses on three types of coffee particles—Type A (145 μm), Type B (100 μm), and Type C (50 μm)—which were mixed with creamer in a weight ratio of 1:0.7. The mixing process was conducted using a prototype fluidized bed mixer with a capacity of 1,000 grams and a blower speed range of 2,800–3,000 rpm. After 10 minutes of mixing, significant reductions in particle size were observed: Type A decreased by 20–30%, Type B by 10–15%, and Type C by 5–10%, with creamer particles also experiencing a 15% reduction. Moisture content dropped from 10.63% to 8.5%, demonstrating the system’s dual function of mixing and drying. Microscopic analysis revealed a uniform particle distribution with minimal agglomeration or segregation, confirming the effectiveness of the fluidized bed mixer in achieving a homogeneous blend. These findings underscore the potential of fluidized bed technology in improving the quality, stability, and handling properties of powder-based products. The results have important implications for instant beverage production, food formulation, and broader powder processing industries, where consistent product performance is essential.